2015
DOI: 10.1007/s00418-015-1390-7
|View full text |Cite|
|
Sign up to set email alerts
|

Phospholipase C-η2 interacts with nuclear and cytoplasmic LIMK-1 during retinoic acid-stimulated neurite growth

Abstract: Neurite growth is central to the formation and differentiation of functional neurons, and recently, an essential role for phospholipase C-η2 (PLCη2) in neuritogenesis was revealed. Here we investigate the function of PLCη2 in neuritogenesis using Neuro2A cells, which upon stimulation with retinoic acid differentiate and form neurites. We first investigated the role of the PLCη2 calcium-binding EF-hand domain, a domain that is known to be required for PLCη2 activation. To do this, we quantified neurite outgrowt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…Using the NeuroA cells as a model for neuronal differentiation by retinoic acid, it was found that PLCε2 activity was required for differentiation. A mutant devoid of PLC activity inhibited differentiation as did knockdown by siRNA [387]. LIMK-1 (LIM domain kinase 1) was found to interact with PLCε2 [387,389].…”
Section: Plc Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Using the NeuroA cells as a model for neuronal differentiation by retinoic acid, it was found that PLCε2 activity was required for differentiation. A mutant devoid of PLC activity inhibited differentiation as did knockdown by siRNA [387]. LIMK-1 (LIM domain kinase 1) was found to interact with PLCε2 [387,389].…”
Section: Plc Familymentioning
confidence: 99%
“…Because PI(4,5)P 2 has multiple functions including regulation of ion channels and actin cytoskeleton and is required for exocytosis, PLCε2 could be an important modulator of neuronal function. The function of PLCε2 has been explored in neuronal cultured cell-lines and results suggest that it may be involved in neuronal differentiation and vesicle exocytosis in neuroendocrine cells [387,388]. Using the NeuroA cells as a model for neuronal differentiation by retinoic acid, it was found that PLCε2 activity was required for differentiation.…”
Section: Plc Familymentioning
confidence: 99%
“…In this study, we observed decreased expression of Limk1 and Tiam1 , which are enzymes known to be associated with rearranging of the cytoskeleton (see scheme in Figure 11) and interact with the retinoid receptor function (Ishaq et al., 2011). Activation of LIMK1 is associated with retinoic acid‐stimulated neurite outgrowth (Arastoo et al., 2016). LIMK1 regulates actin dynamics by phosphorylating cofilin, which contributes to processes of neurite elongation (Reichova et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of LIM kinases integrates signals from a number of Rho GTPases and serves as a link to differentiation processes. One recent study has found that stimulation of Neuro2A cells with retinoic acid results in the differentiation and formation of neurites with corresponding changes of LIM kinase interaction capabilities (Arastoo et al, ). Another downstream effector of Rho GTPases represented by p21‐activated kinases (PAKs), which convey signals to the direct regulators of the actin cytoskeleton (Woolfrey & Srivastava, ).…”
Section: Rho Gtpases Activate the Spectrum Of Signaling Cascadesmentioning
confidence: 99%
“…It is widely discussed that inhibition of RhoA/ROCK in the central nervous system promotes axon growth and regeneration (Fujita & Yamashita, 2014). Some studies claim that ROCK inhibition may be a promising target for neuroprotection and axon regeneration (Van de One recent study has found that stimulation of Neuro2A cells with retinoic acid results in the differentiation and formation of neurites with corresponding changes of LIM kinase interaction capabilities (Arastoo et al, 2016). Another downstream effector of Rho GTPases represented by p21-activated kinases (PAKs), which convey signals to the direct regulators of the actin cytoskeleton (Woolfrey & Srivastava, 2016).…”
Section: Rho Gtpases Have Many Downstream Effectors Including Rocksmentioning
confidence: 99%